Kajian Tingkat Efektivitas Pengelolaan Daerah Perlindungan Laut Berbasis Masyarakat Desa Waha Kabupaten Wakatobi Indonesia - Iskandar, Ishak; Nur, Andi Irwan; Sadarun, Baru (Universitas Halu Oleo, 2018)
Marine Protected Areas (MPAs) are a common management approach that applied to protect and conserve coastal and marine resources in the world. However, in some areas where these approach have been implemented, the goals and targets did not proceed as expected and resulted in methods and objects of study that are relatively irrelevant to the existing conditions. Therefore, a review and more efforts are required to determine the efficacy of the MPAs management. The community based management of marine protected area at Waha Village can be regarded as a manifestation of the local people to meet their needs by utilizing natural resources sustainably. Therefore, this study aims to asses the ecological and socio-economic condition as well as community institutions to determine whether the community based management of the MPA is effective. Ecological data collection was divided into several indicators such as coral reef, seagrass and coral fish community condition that was collected through direct survey using SCUBA. Whereas socio-economic and institutional data was obtained in three stages include observation, semi-structured interviews and surveys. The percentage of live coral cover on MPA of Waha Village was 55,83%. There were 28 species from 9 families and 14 genuses of target fish found in MPA of Waha Village. Seagrass density was 299.87 stands / m2 with average value of seagrass presentation was 63,25%, indicating that seagrass is in good condition. Based on the effectiveness analysis using the Amoeba technique, the indicator values were generally better in performance than the critical threshold value (CTV) indicator. This is because these values have not passed the CTV. The degree of effectiveness of community based management of MPA at Waha Village was 79,17%, suggesting that these management approach is very effective to conserve marine natural resources in the area.Keywords : Effectiveness, management, protected area.